Global Food Prices and Domestic Inflation : Some Cross-Country Evidence - Furceri, Davide (IMF Working Papers; Working Paper, 2015)
This paper provides a broad brush look at the impact of fluctuations in global food prices on domestic inflation in a large group of countries. For advanced economies, we find that these fluctuations have played a significant role over the period from 1960 to the present, but the impact has declined over time and become less persistent. We also find that the more recent global food price shocks occurred in the 2000s had a much bigger impact on emerging than on advanced economies. This larger impact could reflect the larger share of food in the consumption baskets in emerging economies on average than in advanced economies, and less anchored inflation expectations in emerging economies than in advanced economies.